Mengenali kemampuan siswa berdasarkan teori multiple intelligence - Setiorini, Faradina (Maliki Interdisciplinary Journal, 2024)
This research aims to identify students’ abilities based on the Multiple Intelligence theory proposed by Howard Gardner. The research approach used in this research is qualitative with interview and observation methods. The research results show that the application of multiple intelligence theory in the learning process can increase student enthusiasm, creativity and involvement. Although there are several obstacles in its implementation, including limited resources, etc. Implementation of this theory helps students to be more motivated to learn and encourages teachers to use creative and innovative teaching methods